Expeditious assembly of 3,4-benzannulated 8-oxabicyclo[3.2.1]octane systems by [2+2+2] alkyne cyclotrimerisation: Total synthesis of (-)-bruguierol A - Ramana, Chepuri V.; Salian, Sumanth R.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2007)
Facile construction of benzene-fused 8-oxabicyclo[3.2.1]octane systems by employing a cross alkyne cyclotrimerisation reaction was explored. With this procedure, (-)-bruguierol A was synthesised, and its absolute configuration was established.
Keywords: cyclotrimerisation; epoxidation; Total synthesis; Wilkinson's catalyst

[2+2+2]-cyclotrimerization approach for the synthesis of enantiopure isochromans using a carbohydrate derived dialkyne template - Ramana, C. V.; Suryawanshi, Sharad B. (Tetrahedron Letters, 2008)
An easy access to enantiopure isochromans through cross alkyne trimerization of a glucose derived dialkyne was developed. One of the synthesized isochromans was converted into a novel tricyclic nucleoside by simple transformations. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: isochroman; tricyclic nucleoside; Vorbruggen reaction; Wilkinson's catalyst; [2+2+2]-Cyclotrimerization

Total synthesis and structural assignment of hexaketide xylarinolb and its C1-epimer - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Asian Journal of Organic Chemistry, 2016)
The total synthesis of two isomeric hexaketides isolated along with sordarial, which have the proposed relative arabino and ribo configurations, has been executed. A Rh-catalyzed [2+2+2]-alkyne cyclotrimerization has been employed as the key reaction to construct the central dihydroisobenzofuran core. The absolute configuration of the xylarinolB hexaketide has been established as l-arabino. This is the first natural product of this family for which the absolute configuration has been determined, and this can be extended to provide structural details of several of related hexaketides.
Keywords: hexaketides; sordarial; Wilkinson's catalyst; xylarinolB; {[2+2+2]-cyclotrimerization